Personal finance management application - Tan, Le Jie (2024)
Managing personal finances can be challenging due to the lack of personalized feedback, real-time insights, and effective forecasting tools. Individuals often struggle to track their financial health, make informed decisions, and plan for future expenses, especially with the complexity of modern financial trends. After reviewing existing technologies like OpenAI GPT for natural language processing and Facebook Prophet for time series forecasting, along with financial management applications such as Spendee, Money Lover, Expensify, Mint and YNAB, gaps in personalization and dynamic financial insights were identified. These existing tools often lack the capability to provide users with tailored financial advice and accurate, long-term forecasting. In response, this project offers a solution by developing a mobile application that integrates a Personalized Financial Health Score System, an AI-powered chatbot for interactive financial guidance, and predictive analytics to help users better understand and manage their financial health. This app aims to empower individuals to make more informed decisions, offering real-time financial insights and a proactive approach to personal finance management.